Class and Community in Frontier Colorado - Hogan, Richard (University Press of Kansas, 1990)
Spurred by the Gold Rush of 1859, settlers of diverse backgrounds and nationalities trekked to Colorado and began building towns. Existing accounts of their struggles and those of townbuilders throughout the American West focus on boomorbust economics, rampant boosterism, and bitter social conflicts. This, according to sociologist Richard Hogan, is not the whole story.In Class and Community in Frontier Colorado Hogan offers a fresh perspective on the frontier townbuilding experience. He argues that townbuilding in Colorado was not, as some have suggested, monopolized by local boosters or national business interests. It was, instead, a complex, dynamic process that reflected competition, cooperation, and conflict among various socioeconomic classes, and between local and national business interests as well.Hogan shows how farmers, ranchers, miners, tradesmen, merchants, bankers, entrepreneurs, land speculators, and eastern investors all vied for control in six of Colorado's emerging urban centers: Denver, Central City, Greeley, Golden, Pueblo, and Canon City. Meticulously he traces the conflicts and coalitions that arose in and among these groups.By combining historical sociology with local history, Hogan's study challenges current thinking about economic development, class structure and conflict, political partisanship, collective action, and social change in the American West.